Sanksi Adminsitratif Terhadap Notaris yang Menolak Protokol Notaris - Indyravastha Rezhana; Bayu Dwi Anggono; Moh Ali (CV. Syntax Corporation Indonesia, 2021)
Notaries in the performance of their duties have an obligation to accept the protocol of the Notary who quits office. The obligation, although not regulated in the Notary Office Law, is regulated implicitly in the Regulation of the Minister of Law and Human Rights No. 19 of 2019 concerning the Terms and Procedures for appointment, leave, transfer, termination and extension of the term of notary (Permenkumham No. 19 of 2019). This research uses the method... And processed the results that notaries are required to maintain the Notary protocol because it is a category as a state archive. Administrative sanctions for the notary's obligation to receive the protocol have been stated through an affidavit made by the Notary before taking office so that this becomes a binding obligation for the Notary, but it is not specifically mentioned in the relevant legal regulations. The archive of notary protocols in the future should not burden the notary of the recipient of the protocol so that in the future or soon can be realized in the form of file documents or in a more practical form.